2022
DOI: 10.1021/acs.cgd.2c00106
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Electron–Phonon Coupling Dependence on the π-Conjugated Groups in Rare-Earth Borates

Abstract: Electron−phonon (e−ph) coupling, representing an interaction term connecting the electronic states and lattice vibrations, is an important hot topic in physical and chemistry frontiers. However, the e−ph coupling intensity dependence on the structural motifs is not well understood at present. Borate crystal containing conjugated πbonds is an important functional material for optical applications. Here, we investigated the relationship between the e−ph coupling intensity and the π-conjugated borate groups, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In previous work, we found that a “free O” atom, which is only linked to a RE ion but no B atoms, is very effective at improving the electron–phonon coupling effect. Taking the GdCOB crystal as an example, the effective charge of “free O” increases to –0.44, and its Huang–Rhys S factor reaches 0.192 at 300 K, which is much larger than those of rare-earth borates, e.g., Gd:YAB and Ba 3 Gd­(B 3 O 6 ) 3 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous work, we found that a “free O” atom, which is only linked to a RE ion but no B atoms, is very effective at improving the electron–phonon coupling effect. Taking the GdCOB crystal as an example, the effective charge of “free O” increases to –0.44, and its Huang–Rhys S factor reaches 0.192 at 300 K, which is much larger than those of rare-earth borates, e.g., Gd:YAB and Ba 3 Gd­(B 3 O 6 ) 3 …”
Section: Resultsmentioning
confidence: 98%
“…Taking the GdCOB crystal as an example, the effective charge of "free O" increases to −0.44, and its Huang− Rhys S factor reaches 0.192 at 300 K, which is much larger than those of rare-earth borates, e.g., Gd:YAB and Ba 3 Gd-(B 3 O 6 ) 3 . 26 "Quasi-free O" is a natural concept extension based on "free O". In rare-earth borates containing both BO 3 and BO 4 groups, there will be at least two types of O atoms in the crystal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…All of these values are consistent with those acquired from other borates. [20][21][22][23] AgCa 2 B 7 O 11 (OH) 4 crystallizes in the centrosymmetric space group C2/c (Table 1) and it displays borate chains with B 8 O 8 8-MRs along the c axis, with a diameter of 6.4×5.3 Å which can be seen as the crosslinked of B 7 O 16 cluters containing three B 3 O 3 rings by O1-sharing (Figure 3b and 4). The asymmetric unit of 2 contains 0.5 Ag atoms, 1 Ca atom, 7.5 O atoms and 3.5 B atoms (Figure S2b).…”
Section: Resultsmentioning
confidence: 99%
“…Birefringent crystals are of great importance as they can act as various polarization devices such as an optical circulator, electro-optic device, Q switch, beam splitter, and optical isolator, which have wide applications in scientific instrumentation, optical communications, the laser industry, etc. Borates are widely known as an optical material resource in the ultraviolet–visible region, including the “China brand” crystals β-BaB 2 O 4 , LiB 3 O 5 , and KBBF and birefringent materials, such as α-BaB 2 O 4 ( α- BBO), Ba 2 Mg­(B 3 O 6 ) 2 , , Ba 2 Ca­(B 3 O 6 ) 2 , Ba 3 Y­(B 3 O 6 ) 2 , Ca 3 (BO 3 ) 2 , CaB 2 O 4 , etc. Herein, the planar [B 3 O 6 ] group was regarded as an outstanding birefringent gene, which has the largest polarization anisotropy among all borate groups.…”
Section: Introductionmentioning
confidence: 99%